Hi jeremy, I agree with E. First, you have to realize that if (-1)*x = 1, then x=-1
Then, just plug in -1 in each of I, II and III and you will get an integer.
I) -1 / 2+(-1) = -1/1 = -1 --> this is an integer
II) -1-2 / 3 = -3/3 = -1 --> this is an integer
III) -1+1 / 4 = 0/4 = 0 --> this is an integer
Agree with this. The hardest part of the problem is the crappy Kaplan
cd making the equation look stupid. To me, it looks like [(-1)^x]x=1, which means nothing at all. So if that threw you off, don't worry - Kaplan
is often nothing like the real test and you won't have the problem on the real exam.
am I being transparent about my feelings for Kaplan
? I've never been too diplomatic....